2016
DOI: 10.21272/jnep.8(2).02005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing on the Properties of Nanocrystalline CdS Thin Films Prepared by CBD Method

Abstract: The CdS thin films were deposited on glass substrate by chemical bath deposition (CBD). The effect of annealing temperature on the morphological, structural, optical and electrical properties of the crystalline CdS films were investigated for different annealing temperature (as deposited, 300, 400 and 500 °C).The annealing time is 1 h. The materials have been prepared using simple aqueous solutions containing cadmium sulfate, as source of cadmium, and thiourea as source of sulfur and ammonium hydroxide as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The band gap (E g ) was determined by extrapolating the linear portions to the horizontal photon energy axis. 24,25 The calculated optical band gaps of the pure ZnO and ZnO/V 2 O 5 composite thin lms are tabulated in Table 3. The band gap decreased as the concentration of vanadium pentoxide increased.…”
Section: Transmission Electron Microscopy Studiesmentioning
confidence: 99%
“…The band gap (E g ) was determined by extrapolating the linear portions to the horizontal photon energy axis. 24,25 The calculated optical band gaps of the pure ZnO and ZnO/V 2 O 5 composite thin lms are tabulated in Table 3. The band gap decreased as the concentration of vanadium pentoxide increased.…”
Section: Transmission Electron Microscopy Studiesmentioning
confidence: 99%
“…The grain size (D) of undoped and (Al, In) doped ZnO thin films were evaluated to be between 12 nm to 15 nm by using the Debye Scherrer's formula [21]. 3Where  is the full width at half maximum (FWHM) of the diffraction peak;…”
Section: Structural Propertiesmentioning
confidence: 99%
“…A maximum transmittance of 85 % is obtained for undoped ZnO films at around 600 nm, whereas both the IZO and AZO films exhibit a maximum of 80 % at the same wavelength. The energy gap (Eg) of the ZnO films can be calculated by using the relation [26]:…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct band gap is determined using this equation when linear portion of (h)² against h plot is extrapolated to intersect the energy axis at  =0 (Fig. 5) [31,32]. We have found that the value of the energy band gap of the PbTiO3 thin film deposited on MgO is 3.2 eV.…”
Section: Optical Band Gapmentioning
confidence: 99%